Potential therapeutic mechanisms of Draconis Resina in cardiovascular diseases-a narrative review - Wang, Jing; Tang, Xiusong; Lan, Peng; Liang, Bin; Fang, Yu; Li, Hongbo (Frontiers in Pharmacology, 2025)
As a traditional Chinese herbal medicine, Draconis Resina (DR) has garnered significant attention due to its efficacy in treating various clinical diseases. Notably, it demonstrates remarkable therapeutic effects in cardiovascular diseases, such as atherosclerosis, coronary heart disease, and myocardial ischemia-reperfusion injury. A comprehensive understanding of the potential therapeutic mechanisms of DR in cardiovascular diseases can positively influence their prevention and treatment. Therefore, through a thorough literature review, this paper summarizes the primary mechanisms of DR in managing cardiovascular diseases, which include the prevention of thrombosis, inhibition of inflammatory responses, alleviation of oxidative stress, enhancement of endothelial function, and mitigation of myocardial fibrosis. There may remain many untapped therapeutic applications of DR that need further exploration. This review aims to give readers a deeper understanding of the DR and offer new perspectives.